Acorus calamus L. A Potential Medicinal Plant - Mazher, Farheen (Indian Forester, 2013)
Acorus calamus, commonly known as sweet flag, has long been known for its medicinal value. It is cultivated in many countries because of the demand of its essential oil and powder. It is widely employed in modern herbal medicine as an aromatic stimulant and general brain tonic. Main chemical constituents are asarone and Î²-asarone present in rhizome and leaves. The wild source of medicine is shrinking day-by-day. There is a need for conservation and sustainable use of such plant of immense medicinal value.